AN INVESTIGATION INTO THE EFFECTS OF RAPID QUENCHING ON THE SOLIDIFICATION OF AL-CU AND AL-MG ALLOYS - CEYLAN, M; YALVAC, SN; GUNDUZ, M; KARAASLAN, T (Elsevier Science Sa Lausanne, 1994)
Rapidly solidified ribbons and air-cooled casting ingots of Al-Cu and Al-Mg liquids alloys were investigated using the X-ray diffraction method and optical microscopy. The effects of quenching rates on the amorphization have been established by a broad shoulder on the left side in the X-ray diffractograms obtained from powders of the ribbon Al-Mg sample. When comparing the diffractograms obtained from the ingots and the ribbons of both alloys the same crystals structures were encountered. From the shift of the positions of the peaks, it was found that some residual stresses had arisen in the rapidly solidified ribbon samples. The difference between the peak heights of the ribbon and the ingot of Al-Cu alloy shows that the beta-Cu phase in the ribbon is more stable than in the ingot.
Keywords: Amorphous Metals; Behavior; Glasses